Implementasi Metode STEAM Berbasis Media Audio Visual dalam Meningkatkan Aspek Kognitif pada Pendidikan Anak Usia Dini - Abd. Hakim Naba; Nirwana Nirwana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2021)
Abstark. Implementation of Audio Visual Media-Based STEAM Method in Improving Cognitive Aspects in Early Childhood Education. This study aims to describe the implementation of the STEAM method based on audio-visual media in improving cognitive aspects in early childhood. This research method uses a qualitative approach with a qualitative descriptive type of research. The results of this study show that the Audio Visual Media-based STEAM method in Improving Cognitive Aspects in Early Childhood Education in Kindergarten is able to improve children's cognitive development. In addition, audio-visual media is not only as a prop but also as a carrier of information or teaching messages to children.